Caffeine, sleep duration and adolescents’ perception of health related quality of life - Matos, MG (2016)
© 2016 Matos et al.; This is an Open Access article distributed under the terms of the Creative Commons Attribution License (http://creativecommons.org/licenses/by/4.0), which permits unrestricted use, distribution, and reproduction in any medium, provided the original work is properly cited.